2015
DOI: 10.4236/arsci.2015.33006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Cumulus Cell Removal on the Fertilization and Clinical Outcome in Human <i>in Vitro</i> Fertilization

Abstract: The short-term insemination technique has been widely applied, although it is not clear whether the mechanical desorption of cumulus cells can affect normal fertilization and birth outcomes. Therefore, the present study aimed to evaluate whether early cumulus cell removal could affect in vitro fertilization outcomes. Based on a history of infertility and semen analysis, 61 patients were identified, and the cumulus cells were mechanically removed at either6 h post-insemination (Group A, 387 mature oocytes) or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Our results showed that early cumulus cell removal had comparable obstetric and prenatal outcomes with late cumulus cell removal, in agreement with Liu et al [ 14 ]. However, recent studies [ 11 , 13 ] reported higher rates of premature delivery, twins, and low-birth-weight newborns in patients who underwent early cumulus cell removal.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that early cumulus cell removal had comparable obstetric and prenatal outcomes with late cumulus cell removal, in agreement with Liu et al [ 14 ]. However, recent studies [ 11 , 13 ] reported higher rates of premature delivery, twins, and low-birth-weight newborns in patients who underwent early cumulus cell removal.…”
Section: Discussionsupporting
confidence: 93%
“…The ability to draw a clear conclusion may be hindered by differences in study designs and populations. In the present study, sibling oocytes were randomly allocated into two groups to minimize the confounding between patients, and the findings indicated that early cumulus cell removal had no significant difference in fertilization, polyspermy, cleavage of embryos, clinical pregnancy, and ongoing pregnancy, comparable with the findings of previous studies [4,5,[12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 85%
“…15 This study found no significant difference in polyspermy, implantation, and clinical pregnancy rate in short and long co-incubation as previous studies. [9][10][11][12][13] In the short co-incubation and early cumulus cell removal, the patient had a higher premature delivery, twins and low birth weight newborn than long coincubation. 5,[11][12][13] Li et al, pointed out that cumulus cell removal at a different time can alter spindle integrity and impair cell division which results in twins or poor fetal growth.…”
Section: Resultsmentioning
confidence: 98%
“…Zhou and Liu (co-incubation 6 hours) found that implantation rate and clinical pregnancy rate were similar to long co-incubation. [4][5][6][9][10][11][12][13] In contradiction, Barraud-Lange et al, demonstrated that short co-incubation had low numbers of available embryos for transfer. 14 Nevertheless, a meta-analysis indicates that short coincubation has a significant increase in implantation rate and clinical pregnancy rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation